2023
DOI: 10.3389/fmicb.2023.1200226
|View full text |Cite
|
Sign up to set email alerts
|

Dazomet changes microbial communities and improves morel mushroom yield under continuous cropping

Abstract: Morels (Morchella spp.) are highly prized and popular edible mushrooms. The outdoor cultivation of morels in China first developed at the beginning of the 21st century. Several species, such as Morchella sextelata, M. eximia, and M. importuna, have been commercially cultivated in greenhouses. However, the detriments and obstacles associated with continuous cropping have become increasingly serious, reducing yields and even leading to a complete lack of fructification. It has been reported that the obstacles en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…For instance, the alteration of soil physicochemical properties serves as a primary causative factor in the occurrence of continuous cropping obstacles in Panax ginseng cultivation [21]. The occurrence of continuous cropping obstacles in Morels cultivation may be associated with variations in soil microbial community structure [22]. Moreover, continuous cropping also changes the components of Sesamum indicum root exudates [23].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the alteration of soil physicochemical properties serves as a primary causative factor in the occurrence of continuous cropping obstacles in Panax ginseng cultivation [21]. The occurrence of continuous cropping obstacles in Morels cultivation may be associated with variations in soil microbial community structure [22]. Moreover, continuous cropping also changes the components of Sesamum indicum root exudates [23].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that the possible reasons for the decline in mushroom production include unstable bacterial quality, improper field management methods, adverse environmental factors, pathogenic bacteria, soil characteristics, and soil microbial community dynamics [14][15][16][17]. Several studies have shown the obstacles associated with continuous cropping effects of conjunctions on mushroom yield [18]. The root cause of the obstacles associated with continuous cropping is a decrease in mushroom production due to changes in its microbial community [13].…”
Section: Introductionmentioning
confidence: 99%